Family values of Vietnamese living in Vietnam and Poland - Mai Van Hai (Acta Universitatis Lodziensis. Folia Psychologica, 2018)
This article focuses on the results of the study on family values of Vietnamese living in Vietnam and Poland. The participants were 196 Vietnamese (100 people in Vietnam, 96 people in Poland) and 15 people who got married with Poles. The methods used included questionnaire and intensive interview. The study used traditional family values of Vietnamese as the background for data analyses and comparison of two groups. The study results showed that Vietnamese participants continued to confirm basic traditional family values such as filial piety, respect for parents, especially in parents – offspring relations; faithfulness, benevolence and righteousness in husband – wife relations. Besides, some differences were revealed such as participants living in Poland having more freedom than other group in relationships with offspring, and are more flexibility in opinions and behavior about sex issues. These findings confirm that living and working overseas bring some changes to the system of accepted family values.